2018
DOI: 10.1007/s40263-018-0508-6
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Acting Injectable Second-Generation Antipsychotics: An Update and Comparison Between Agents

Abstract: Schizophrenia is a chronic medical condition with periods of remission and relapses over a patient's lifetime. Antipsychotic medications represent the mainstay of treatment for this disease. Long-acting injectable (LAI) formulations of antipsychotics are an attractive alternative to their oral counterparts, as they enhance patient adherence. A number of second-generation antipsychotics (SGAs) are available in LAI formulations. These include paliperidone, aripiprazole, olanzapine, and risperidone. This article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 71 publications
0
20
0
1
Order By: Relevance
“…As the few direct comparison studies of depot/LAI antipsychotic preparations have not revealed much difference in terms of efficacy between those tested (Li et al, 2011; McEvoy et al 2014; Pandina et al, 2011), the nature of the side-effect burden is probably the primary criterion for choosing a particular medication. The adverse effects include uncomfortable local reactions at the injection site, characterised by pain, inflammation and induration, which have been estimated to occur in up to 15–20% of patients a year (Bloch et al, 2001; Hay, 1995; Jones et al, 1998), although lower rates with LAI SGAs have been reported more recently (Atkins et al, 2014; Jann and Penzak, 2018). Jones et al (1998) suggested that the risk of such reactions with FGA depot/LAIs might be minimised by the use of low-volume preparations and increasing the interval between injections.…”
Section: Maintaining Responsementioning
confidence: 99%
“…As the few direct comparison studies of depot/LAI antipsychotic preparations have not revealed much difference in terms of efficacy between those tested (Li et al, 2011; McEvoy et al 2014; Pandina et al, 2011), the nature of the side-effect burden is probably the primary criterion for choosing a particular medication. The adverse effects include uncomfortable local reactions at the injection site, characterised by pain, inflammation and induration, which have been estimated to occur in up to 15–20% of patients a year (Bloch et al, 2001; Hay, 1995; Jones et al, 1998), although lower rates with LAI SGAs have been reported more recently (Atkins et al, 2014; Jann and Penzak, 2018). Jones et al (1998) suggested that the risk of such reactions with FGA depot/LAIs might be minimised by the use of low-volume preparations and increasing the interval between injections.…”
Section: Maintaining Responsementioning
confidence: 99%
“…There has been hope that use of long‐acting injectable (LAI) or depot preparations of antipsychotic medications would increase long‐term treatment‐adherence and enhance the effectiveness of treatment. Such agents started with esters of fluphenazine and haloperidol in the 1960s and 1970s, followed by additional esters as well as agents made long‐acting by other pharmacological mechanisms (Baldessarini, 2013; Haddad, Brain, & Scott, 2014; Jann & Penzak, 2018; Johnson, 2009). There was a resurgence of interest in LAI antipsychotics after the launch of risperidone in a LAI form based on its incorporation into slowly hydrolyzed carbohydrate microspheres (Sampson, Hosalli, Furado, & Davis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia is a widespread mental disorder with periods of remission and relapses over a patient's lifetime (van Os and Kapur, 2009;Jann and Penzak, 2018), and long-term treatment with antipsychotic drugs is often required (Kahn et al, 2015). The lifetime prevalence of schizophrenia in Chinese population is 0.9% (Huang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%